Development of evaporative cooling battery thermal management system for electric vehicles - Ahmad Hilmi bin Khalid (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
Battery pack needs to generate a high output within a very short time to meet the power demand of an electric vehicle when it is in acceleration. High discharge current causes significant warming of the Li-ion cells due to internal resistance within the cells. LiFePO4 batteries, however, can be used efficiently only within an operating temperature in the range of 20ºC to 40ºC. The life span and lifecycle of the battery will reduced significantly if the temperature goes above the recommended range. The rationale of this study is to develop an innovative evaporative cooling battery thermal management system (EC-BThMS) to control the battery temperature in the range of 20ºC to 40ºC. The simplified mathematical equations have been developed in this study for the kinematics analysis and simulation to investigate the temperature profile of the battery based on discharge current drawn, total heat generation and total heat dissipation from the battery. The performance investigation of the EC-BThMS has been conducted both theoretically and experimentally during discharging mode. Theoretically, it was found that the battery temperature varies from 26.5ºCto 31ºCfor discharge current in the range of 40 A to 100 A. Experimentally, testing results in IIUM campus road found that the battery temperature varies from 28ºC to 34ºC for discharge current in the range of 35 A to 120 A. While testing results in Sepang International Circuit (SIC) showed that the battery temperature was in the range of 26ºC to 35ºCfor discharge current in the range of 60 A to 80 A. The performance of developed EC-BThMS in SIC has also been compared with two types of air cooling battery thermal management systems (AC-BThMS) used in others Proton Saga EV. It was found that the Proton Saga EV with EC-BThMS can save 17.69% more energy than with AC-BThM 1 and 23% than with AC-BThMS 2. The correlations between the measured and predicted values of temperature profiles of the battery during operation have been found to be 97.3%. This is indicates that the predicted data over the measured data have a closed agreement and thus, substantially verified the mathematical model.